2013
DOI: 10.1186/1471-2458-13-582
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer risk factors among HIV-infected Nigerian women

Abstract: BackgroundCervical cancer is the third most common cancer among women worldwide, and in Nigeria it is the second most common female cancer. Cervical cancer is an AIDS-defining cancer; however, HIV only marginally increases the risk of cervical pre-cancer and cancer. In this study, we examine the risk factors for cervical pre-cancer and cancer among HIV-positive women screened for cervical cancer at two medical institutions in Abuja, Nigeria.MethodsA total of 2,501 HIV-positive women participating in the cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
55
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 48 publications
13
55
7
Order By: Relevance
“…However, the finding is in contrast to the reports of Liu et al (2016) in Tanzanian and Ononogbu et al (2013) in Abuja, Nigeria who found a significant association between increasing age and the risk of developing premalignant lesions of the cervix among the women.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, the finding is in contrast to the reports of Liu et al (2016) in Tanzanian and Ononogbu et al (2013) in Abuja, Nigeria who found a significant association between increasing age and the risk of developing premalignant lesions of the cervix among the women.…”
Section: Discussioncontrasting
confidence: 56%
“…Similarly, Ononogbu et al (2013) studied 2501 HIV positive women in Abuja, Nigeria and reported that increasing age and age >40 years were associated with reduced risk of developing premalignant lesions of the cervix among the women.…”
Section: Introductionmentioning
confidence: 99%
“…12 The younger age of presentation of ICC among HIV-seropositive women has been also reported in several smaller studies in sub-Saharan Africa. 1315,29,30 However, in a study done in Dakar, Senegal, an increase in ICC was noted only in women above the reproductive age, 55 years and above. 28 This is perhaps due to the higher prevalence of HIV-2 in this population (compared with HIV-1, which is more prevalent in Southern Africa); since HIV-2 has a long latent period and slower progression to AIDS.…”
Section: Discussionmentioning
confidence: 94%
“…911 It has been reported from previous smaller and retrospective studies from sub-Saharan Africa that HIV-seropositive women typically present with ICC at an earlier age. 1215 This likely results from a more rapid progression of chronic persistent human papillomavirus infection in this subpopulation, modulated by a relative immunosuppressive state (even while accessing ART), 16,17 and is further accentuated by the limited or nonexistent access to cervical cancer screening services.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer prevention initiatives that harness HIV treatment and prevention programs are likely to be the most cost effective and also to have the broadest impacts. 21-23 The increased professional and public awareness of cancer in LMICs as a treatable and preventable comorbidity in people with controlled HIV infection is likely to have spin-off benefits to the general population by strengthening general oncologic practice and cancer registration, increasing our understanding of the spectrum of cancers, and characterizing trends in cancer incidence. 24 …”
Section: Evolutionmentioning
confidence: 99%